Impact of Farmer’s Training Programs on the Promotion of Alfalfa Cultivation in Ghayathi, United Arab Emirates - Arshad, Imran; Khan, Zaheer Ahmed; Ali, Wajiha (PSM Biological Research, 2023)
In this research work the impact of farmers training programs on the promotion of alfalfa cultivation in Ghayathi, UAE was studied. This study was undertaken with a view on 100 participants selected by random sampling technique. The respondents attended trainings and pre-test and post-test knowledge before and after training was conduction to check the perception level of the farmers. The results of the study revealed that majority (92%) of the respondents recommended that the efficiency of their work could be improved by offering them such kind of training courses related to alfalfa cultivation. The maximum change in perception level of 79.47% and 76.31% was found in flowering and sprouting and seed collection respectively. Providing information, technical training sessions and local support from the concern authorities will be of enormous use in the proper adaption of technology was the most common recommendation came from the participants.